Cost-productivity analysis of South African pine sawtimber mechanised cut-to-length harvesting. Issue 4 (1st October 2016) - Williams, Chloe; Ackerman, Pierre
Abstract : The South African forestry industry is experiencing an increase in the number of fully mechanised timber-harvesting systems. Understanding the productivity of these systems, for which data is currently limited for South Africa, is an important step to maximise the utilisation of machines being used. A time study of a mechanised cut-to-length system was conducted in Pinus elliottii sawtimber plantations in the Southern Cape forestry region of South Africa. A harvester and a forwarder were studied with the intention of analysing the division of work time amongst work elements, modelling each machine's productivity and cost, and estimate fuel consumption. For the harvester's productivity, a multiple regression model was developed using diameter at breast height (DBH), average distance moved per work cycle and slope class as predictors (adjusted R 2   = 0.80). The harvester had a mean productivity of 33.6 m 3 per productive machine hour (PMH0 ) under the current conditions with most of the productive time being used in the moving element. It consumed 25.5 L PMH0 −1 of diesel on average. The forwarder's fuel consumption was calculated as 16.8 L PMH0 −1, while productivity was 46.8 m 3 PMH0 −1 . The forwarder spent the longest portion of the work cycle in the loading and unloading phases. A productivity regression model was created that included load size and distance moved during the driving in the loaded phase (adjusted R  2 = 0.78).